The Value Chain and Benefit Distribution in East Java's Goat Meat Business for Sustainable Management - Mujahid; Ramlawati; Arminas; Safar, Ilham; Fahlevi, Mochammad (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2024)
This research evaluates the value chain and benefit distribution within the goat meat industry in East Java, Indonesia, which is becoming a critical component of the country's livestock sector. A total of 120 goat farmers, three retailers, three wholesalers, twelve intermediaries, three slaughterhouses, three processors, and twelve consumers from three districts in East Java were selected as respondents. Snowball sampling and a purposive approach were employed to gather relevant data. The findings re-vealed two distinct value chains in the goat meat industry, with intermediaries playing a crucial role in both. The shortest value chain involved farmers, intermediaries, and consumers, while longer chains included additional actors such as slaughterhouses. The study found that farmers contributed signifi-cantly to the value chain, and as the chain lengthened, consumers demonstrated a willingness to pay higher prices. These findings indicate that strengthening and growing the goat meat supply chain is cru-cial for the industry's long-term development. Key recommendations include boosting goat production and improving the supply chain's effectiveness to satisfy domestic meat consumption while ensuring fair distribution of benefits among all participants.